Infection for Enterobius vermicularis in kindergarten children of rural communities - Talledo, Rodolfo (1999)
A group of 123 children aged 3 to 6 was chosen to study the effects that Enterobius vermicularis infection has on the school children's educational output. These children were the whole pre-scholar population of the kindergarten rural community in Carabayllo and Santa Rosa de Quives in Lima, Perú. This study included a parasitologic and nutritional examination of the children, using the modified Graham's techniques and the nutritional method of Kanawati-Mc Laren. The result was 34,14 per cent of children with Enterobius vermicularis, and 18,08 per cent with a light protein-caloric malnutrition. The relation between the results from the varianza analysis enables us to conclude that Enterobius vermicularis infection does not have an effect on the children's performance in the school; however we can not generalize on this result because no other intestinal parasites were examined and the initial development is more motional than intelectual. Malnutrition was present in children of 5 years old and not in those of 3 and 4 years old who go to school according to our pre-scholar system and the method was not adequate.